2014
DOI: 10.1007/s00432-014-1675-6
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer activity of the Aurora A kinase inhibitor MK-5108 in non-small-cell lung cancer (NSCLC) in vitro as monotherapy and in combination with chemotherapies

Abstract: Purpose Aurora kinases are key regulators of mitotic events. Dysfunction of these kinases can cause polyploidy and chromosomal instability, a contributor to tumorigenesis. MK-5108 is a potent inhibitor of Aurora A kinase that has shown preclinical potent activity in malignancies of breast, cervical, colon, ovarian, and pancreatic origin. We sought to assess the preclinical efficacy of MK-5108 in a panel of non-small-cell lung cancer cell lines as a single agent and in combination with cisplatin and docetaxel. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“… 15 16 Overexpression of AURKA promotes cell proliferation through G1/S cell cycle transition and to antiapoptosis, and can cause polyploidy and chromosomal instability, xenograft tumour growth and chemoresistance. 17 18 Simultaneous inhibition of AURKA and AURKB results in a dramatic decrease in spindle microtubule stability. 19 The human AURKA gene maps to 20q13, a region frequently amplified in breast cancers and is also overexpressed in several tumours.…”
Section: Discussionmentioning
confidence: 99%
“… 15 16 Overexpression of AURKA promotes cell proliferation through G1/S cell cycle transition and to antiapoptosis, and can cause polyploidy and chromosomal instability, xenograft tumour growth and chemoresistance. 17 18 Simultaneous inhibition of AURKA and AURKB results in a dramatic decrease in spindle microtubule stability. 19 The human AURKA gene maps to 20q13, a region frequently amplified in breast cancers and is also overexpressed in several tumours.…”
Section: Discussionmentioning
confidence: 99%
“…References GSK690693 0.4, 2, 10 AKT/PKB 1, 2, 3 (Levy et al, 2009;Rhodes et al, 2008) VX-689 (MK5108) 0.2, 1, AURORA A (Chinn et al, 2014;Shimomura et al, 2010) CYC116 0.4, 2, 10 AURORA A, B (Jayanthan et al, 2014;Wang et al, 2010) ARC-775 0.4, 2, 10 CK2 (Rahnel et al, 2017) ARC-1859 0.4, 2, 10 CK2 (Viht et al, 2015) SGI-1776 0.4, 2, 10 PIM 1, 3 (Chen et al, 2011(Chen et al, , 2009 H89 0.4, 2, 10 PKAc, PKG1 (Dabizzi et al, 2003;Yoshino et al, 2003) Y-27632 0.4, 2, 10 ROCK 1, 2 (Grewal et al, 2010;Yotova et al, 2011;Yuge et al, 2007) HA-1077 (fasudil) 0.4, 2, 10 ROCK 2 (Tsuno et al, 2011) sorafenib (BAY 43-9006) 0.4, 2, 10 RAF1, BRAF, KDR (VEGFR2), FLT4…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…Current studies primarily targeted AURKA. In vitro studies with NSCLC cell lines indicated that the AURKA inhibitor MK-5108 promises to be a potent drug in combination with docetaxel (21). However, clinical trials with the AURKA inhibitors VX-680 and AT9283 had to be terminated because of severe toxicities in patients with chronic myelogenous leukemia (22).…”
Section: Introductionmentioning
confidence: 99%